2018
DOI: 10.3390/antibiotics7030069
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Nanosilver against Multidrug-Resistant Bacteria (MDRB)

Abstract: Multidrug-resistant bacteria (MDRB) are extremely dangerous and bring a serious threat to health care systems as they can survive an attack from almost any drug. The bacteria’s adaptive way of living with the use of antimicrobials and antibiotics caused them to modify and prevail in hostile conditions by creating resistance to known antibiotics or their combinations. The emergence of nanomaterials as new antimicrobials introduces a new paradigm for antibiotic use in various fields. For example, silver nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 157 publications
(127 reference statements)
2
69
0
Order By: Relevance
“…Further, the copolymer biomaterials synthesized with high antibacterial activity against E. coli and S. aureus. These all reports concluded that the biogenic silver nanoparticles are used in combat against multidrug resistant bacterial infection [29].…”
Section: Application In Multi-drug Resistant Therapymentioning
confidence: 99%
“…Further, the copolymer biomaterials synthesized with high antibacterial activity against E. coli and S. aureus. These all reports concluded that the biogenic silver nanoparticles are used in combat against multidrug resistant bacterial infection [29].…”
Section: Application In Multi-drug Resistant Therapymentioning
confidence: 99%
“…A convenient and practical approach where the nutritional quality, sensorial properties, color, and shelf life of the grains remain unchanged is warranted in curbing this menace. Therefore, we propose nanoparticles as the ultimate solution to the predicament mentioned above since they are known to exert potent biocidal activities against the vast myriad of microorganisms [7][8][9][10][11][12][13][14][15][16][17] involves in contaminating grains, hence could be utilized as antifungal agents during grain storage.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of metallic nanoparticles has been described in a range of organisms spanning plants, fungi, and bacteria, often through metal-toxicity resistance mechanisms. (16)(17)(18)(19) Whilst the processes for many of these remain poorly understood, they hold great potential for more environmentally friendly and up-scalable production of AgNP than chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of review articles have been authored which give useful overviews of bacteriogenic metallic nanoparticle synthesis. (14,15,(17)(18)(19)(20)(21)(22) However, to date, no in-depth summary of findings has been published relating to the reaction conditions under which AgNPs are synthesised and the impact that these conditions have on the products. Therefore, this article aims to bring together such results and discuss how biosynthetic reaction parameters can be used to optimise AgNP production with a focus on shape and size control.…”
Section: Introductionmentioning
confidence: 99%